Kulturräumliche Strukturwandlungen am Volta River - Frischen, Alfred; Manshard, Walther (ERDKUNDE, 1971)
This paper outlines the changes in the pattern of human and economic geography that have occurred as a result of the construction of Lake Volta, biggest man-made lake of the earth. In a sketch of the ethnic and demographic base line conditions of the middle-belt in South-Eastern Ghana in the decades before the flooding, emphasis is laid on agricultural migrations (particularly those of the Konkamba). An account of recent developments in the Lake Volta region follows. The Ghana Government Resettlement Programme is described in connection with agricultural progress in the, region. Conditions in a number of sample villages are analysed. In a hitherto nearly uninhabited and rather remote region of economic stagnation, there are now prospects of more active economic growth which may lead to the development of a new economic island in Ghana.